Value Oriented Shopping Behavior Amongstst Urban Middle Class Vietnamese Consumers - Mark , William Speece; Nair, Godwin (Asian Academy of Management (AAM), 2000)
Asia’s economic crisis has caused many middle class consumers to watch their budgets more closely. However, this is not the same thing as consumers becoming highly price conscious, with price as the top criteria in making brand choice. Asia’s modem middle class is strongly value oriented, balancing quality of product characteristics against price. The economic crisis has not changed this. Although Vietnam has not yet been hit as hard as many other Asian countries, it starts with much lower incomes than most other countries, and the economy has slowed down substantially. Yet even in Vietnam, recent surveys show that the strong value orientation continues. Price is not the most important attribute that most consumers consider, but neither do consumers disregard it completely. Most consumers think various product attributes are the most important things to consider, while price is usually near the middle of the attributes, list, not at the bottom. These patterns, though measured on several different types of scales in these surveys, are all consistent with strong value orientation.